Terapi Non Farmakalogis untuk Mengurangi Kecemasan pada Pasien Kanker dengan Kemoterapi: A Systematic Review - Andrik Hermanto; Tintin Sukartini; Esti Yunitasari (FORIKES, 2020)
Background: Anxiety will affect the cancer patient's physiology and decrease the body's immune system, so that intervention is needed to alleviate anxiety. Objective: To find out various non-pharmacalogical therapies to reduce anxiety in cancer patients with chemotherapy. Method: The database used in this study was scopus, proquest and pubmed were limited to the last 5 years of publication from 2016 to 2020, full-text article and in english. The keywords used were